Synthesis and study on biological activity of nitrogen-containing heterocyclic compounds – regulators of enzymes of nucleic acid biosynthesis - Alexeeva, I.V.; Shved, A.D. (Вiopolymers and Cell, 2013)
Results of investigations on the development of new regulators of functional activity of nucleic acid biosynthesis enzymes based on polycyclic nitrogen-containing heterosystems are summarized. Computer design and molecular docking in the catalytic site of target enzyme (T7pol) allowed to perform the directed optimization of basic structures. Several series of compounds were obtained and efficient inhibitors of herpes family (simple herpes virus type 2, Epstein-Barr virus), influenza A and hepatitis C viruses were identified, as well as compounds with potent antitumor, antibacterial and antifungal activity. It was established that the use of model test systems based on enzymes participating in nucleic acids synthesis is a promising approach to the primary screening of potential inhibitors in vitro.